Meningkatkan Aktivitas dan Hasil Belajar Siswa dengan Menerapkan Pembelajaran Kooperatif Model Think Pair Share Berbasis Kurikulum 2013 - Achmad Alfian Irawan; Djoko Dwi Kusumajanto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
This research aims to determine the Increase Activity and Student’s Results in Analysis and Market Research subject for the tenth grade students of Marketing 1 at SMK Negeri 1 Pasuruan in 2014/2015 academic year. The type of this research is classroom action research (CAR). Subjects are the tenth grade students of Marketing 1 class X SMK 1 Pasuruan in 2014/2015 academic year. Data collection was done by using tests, observations, field notes, interviews, student questionnaire responses and documentation. The research is implemented within two cycles. Each cycle includes four phases of activities, which are: 1) planning the action, 2) implementing the action, 3) observation, and 4) reflection. The research findings showed that the implementation Think Pair Share that is: (a) thinking, (b) pairing (c) sharing. Results of the research showed that (1) Implementation of the learning goes well, as evidenced by an increase in activity and student learning outcomes, (2) learning activities of students increased from 37.91% the percentage of the first cycle to 87.60% in the second cycle, (3) the results of student learning consists of cognitive, affective, and psychomotor percentage 44.19% increase from the first cycle to 85.56% in the second cycle (4) barriers that occur can be overcome with the reflection solutions in the form of advice from teachers subjects and observer (5) The response of students to the implementation of cooperative learning model of TPS to get a good appreciation and enthusiasm by the students with an average value of percentage of 87.76%. One of the constraints of the application of the learning model think pair share that need better time management so that teachers should be more careful in managing time.Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan aktivitas dan hasil belajar siswa dalam mata pelajaran analisis dan riset pasar kelas X Pemasaran 1 semester genap 2014/2015 di SMK PGRI 3 Malang. Jenis penelitian ini merupakan penelitian tindakan kelas (PTK). Subyek penelitian adalah siswa kelas X Penasaran 1 SMK Negeri 1 Pasuruan tahun 2014/2015. Pengumpulan data menggunakan tes, observasi, catatan lapangan, wawancara, angket dan dokumentasi. Penelitian ini dilaksanakan dengan dua siklus. Setiap siklus mencakup 4 tahap kegiatan yaitu: 1) perencanaan, 2) pelaksanaan tindakan, 3) observasi dan 4) refleksi. Hasil penelitian menunjukkan bahwa  penerapan model Think Pair Share yaitu: (a) Berfikir mandiri (b) Berpasangan (c) berbagi. Hasil dari penelitian menunjukkan (1) Penerapan pembelajaran berjalan dari dengan baik, terbukti dengan adanya peningkatan pada aktivitas dan hasil belajar siswa, (2) Aktivitas belajar siswa meningkat dari persentase 37,91% pada siklus I menjadi 87,60% pada siklus II, (3) Hasil belajar siswa terdiri dari kognitif, afektif, dan psikomotor yang meningkat dari persentase 44,19% pada siklus I menjadi 85,56% pada siklus II (4) Hambatan  yang terjadi dapat diatasi dengan adanya solusi dalam refleksi berupa saran dari guru mata pelajaran dan observer (5) Respon siswa terhadap penerapan pembelajaran kooperatif model TPS mendapatkan apresiasi dan antusias yang baik oleh siswa dengan nilai presentase rata-rata 87,76%. Salah satu kendala penerapan model pembelajaran think pair share yaitu memerlukan manajemen waktu yang lebih baik sehingga guru harus lebih cermat dalam memanajemen waktu.